Genetic diagnosis and sperm retrieval outcomes for Chinese patients with congenital bilateral absence of vas deferens. (25th February 2020) - Wang, Hongxiang; An, Miao; Liu, Yidong; Hu, Kai; Jin, Yan; Xu, Shiran; Chen, Bin; Lu, Mujun
Abstract: Background: Congenital bilateral absence of the vas deferens (CBAVD) is a frequent cause of obstructive azoospermia. CBAVD is mainly caused by mutations in the CFTR (cystic fibrosis transmembrane conductance regulator) gene and is also related to the X‐linked ADGRG2 (adhesion G protein‐coupled receptor G2) gene. Genetic screening and counseling strategies for Chinese CBAVD populations remain controversial because the genetic background of CBAVD in Chinese population is largely unknown. Objectives: In this study, we aimed to study the mutation spectrum of CFTR and ADGRG2 in a group of CBAVD patients and to evaluate sperm retrieval outcomes in a subset of CBAVD patients. Materials and methods: Next‐generation targeted sequencing was used to identify mutations in the CFTR and ADGRG2 genes in 38 CBAVD patients. In addition, we followed and analyzed nine of the 38 patients who were undergoing sperm retrieval surgery. Results: In total, 27 of 38 (71.05%) patients carried at least one likely pathogenic or pathogenic mutation in CFTR or ADGRG2 . In addition to the IVS9‐5T allele, 15 CFTR and 1 ADGRG2 mutations were identified, including 4 novel mutations. CFTR hot‐spot mutations were not identified in our study. Spermatozoon was successfully obtained in all nine patients who underwent MESA or TESE surgery, but most patients had spermatozoa with relatively low motility and high abnormality rates. Discussion and conclusion: Except for the IVS9‐5T allele, hot‐spot mutations of CFTR may not exist in Chinese CBAVD patients. Therefore, next‐generation targeted sequencing for whole CFTR and ADGRG2 gene may be the appropriate genetic testing method, and genetic counseling may be different from Caucasian populations. We observed a high success rate of sperm retrieval with relatively low motility and high abnormality rates in Chinese CBAVD patients. However, this is only a weak conclusion due to the small sample size.